2012
DOI: 10.1016/j.neuron.2012.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ Block of Drosophila NMDA Receptors Is Required for Long-Term Memory Formation and CREB-Dependent Gene Expression

Abstract: SUMMARY NMDA receptor (NMDAR) channels allow Ca2+ influx only during correlated activation of both pre- and postsynaptic cells; a Mg2+ block mechanism suppresses NMDAR activity when the postsynaptic cell is inactive. Although the importance of NMDARs in associative learning and long-term memory (LTM) formation has been demonstrated, the role of Mg2+ block in these processes remains unclear. Using transgenic flies expressing NMDARs defective for Mg2+ block, we found that Mg2+ block mutants are defective for LTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 54 publications
4
97
1
Order By: Relevance
“…The role of NMDARs in learning and memory processes was also demonstrated in several other invertebrates (Müssig et al 2010;Amano and Maruyama 2011;Miyashita et al 2012;Hepp et al 2013). In our laboratory, research performed in the crab Neohelice granulata (formerly Chasmagnathus granulatus) using context associative learning (context signal memory, CSM) has indicated that NMDA-like receptors are involved in consolidation and reconsolidation (Pedreira et al 2002;Troncoso and Maldonado 2002).…”
mentioning
confidence: 82%
“…The role of NMDARs in learning and memory processes was also demonstrated in several other invertebrates (Müssig et al 2010;Amano and Maruyama 2011;Miyashita et al 2012;Hepp et al 2013). In our laboratory, research performed in the crab Neohelice granulata (formerly Chasmagnathus granulatus) using context associative learning (context signal memory, CSM) has indicated that NMDA-like receptors are involved in consolidation and reconsolidation (Pedreira et al 2002;Troncoso and Maldonado 2002).…”
mentioning
confidence: 82%
“…The amount of CG9134 transcript was normalized to that of a housekeeping gene, Glyceraldehyde 3 phosphate dehydrogenase 1 (Gapdh1) (Miyashita et al 2012). The primers used to amplify CG9134 were 59-GGA GAGTGACTGCGATTGGTTTG-39 and 59-TGTTGCTGCTTT TCGGTCCTG-39.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…As a possible molecular mechanism underlying the memory, the cAMP response element binding protein (Ci-CREB) is important for memory formation in the larval neurons of some animals (Chen et al, 2010;Imai et al, 2004;Kandel, 2004;Miyashita et al, 2012;Yamada et al, 2003). Nitric oxide synthase expressed in the central nervous system (CNS) is another candidate, as it is involved in synaptic potentiation to form memory in mice (Comes et al, 2007;Lange et al, 2012).…”
Section: Larvae Can Remember the Experience Of Adhesionmentioning
confidence: 99%